Assessment of the midgut microbiota in foragers of the stingless bee Melipona scutellaris following short-term sublethal exposure to imidacloprid - Patricia Azevedo; Lucas Miotelo; Manuela Oliveira Ramalho; Tatiane Caroline Grella; Osmar Malaspina; Matthew Hudson; Roberta Cornélio Ferreira Nocelli; Maria Imaculada Zucchi (PLoS ONE, 2025)
The insecticide imidacloprid, widely used in Brazil, is known to have adverse effects on bee populations at both lethal and sublethal doses and concentrations. While previous studies have reported disruption of bee gut microbial communities following pesticide exposure, the effects of short-term sublethal exposure in stingless bees remain unclear. This study evaluated the impact of sublethal concentrations of imidacloprid (LC 50/100 and LC 50/1000 ) on the midgut microbiota composition of the stingless bee Melipona scutellaris . Using metabarcoding of the V3 and V4 regions of 16S rRNA to characterize bacterial community composition and diversity, we analysed midgut bacterial communities of bees collected directly from hives (T0 group) and after 24 and 48 hours of oral imidacloprid exposure. Our results showed that, after 24 and 48 hours of exposure, there were no significant changes in midgut bacterial diversity or composition between bees exposed to sublethal concentrations of imidacloprid and their respective controls. In contrast, we observed clear differences in both diversity and abundance between the T0 group and control groups, especially after 24 hours of incubation. These differences were primarily associated with shifts in Acetobacteraceae family, likely reflecting the influence of the artificial sucrose diet provided under laboratory conditions. It is important to note that our findings pertain only to acute effects. Future studies would benefit from extending the duration of exposure and including a broader range of toxicological endpoints to build on these findings. Our results also underscore the importance of evaluating both exposure period and dietary conditions when investigating pesticide impacts on bee microbiota.